1996
DOI: 10.1007/s004210050110
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a physical activity questionnaire in the elderly

Abstract: The purpose of this study was to validate a physical activity (PA) questionnaire, Questionnaire d'Activité Physique Saint-Etienne (QAPSE), in an homogenous population of elderly subjects and to estimate its potential for application in routine PA assessments in that age group. A group of 65 (31 men and 34 women) community dwelling, healthy people aged 65-84 years volunteered to participate in a validation substudy comparing maximal oxygen uptake (VO2 max) and anthropometric data. VO2 max correlated positively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…If exercise was non-differentially misclassified in our data, 2% would be an underestimate of the true magnitude of the upward confounding bias and the true adjusted hazard ratio would be lower than what we observed. Validation studies of specific physical activity instruments have shown significant correlations between older subjects’ responses and objectively measured physiologic parameters indicating regular physical activity21, 22 as well as with results from “gold standard” doubly-labeled water experiments 23. While our assessment of exercise habits relied on none of the particular instruments examined by the validation studies, our question to participants was detailed and specific in nature and should be of similar validity.…”
Section: Discussionmentioning
confidence: 95%
“…If exercise was non-differentially misclassified in our data, 2% would be an underestimate of the true magnitude of the upward confounding bias and the true adjusted hazard ratio would be lower than what we observed. Validation studies of specific physical activity instruments have shown significant correlations between older subjects’ responses and objectively measured physiologic parameters indicating regular physical activity21, 22 as well as with results from “gold standard” doubly-labeled water experiments 23. While our assessment of exercise habits relied on none of the particular instruments examined by the validation studies, our question to participants was detailed and specific in nature and should be of similar validity.…”
Section: Discussionmentioning
confidence: 95%
“…Self-administered postal versions had results above the recommended standard. Evidence of excellent test-retest results were found for the QAPSE and Zutphen (Bonnefoy et al, 1996;Loland;Voorrips et al, 1991;Washburn et al, 1993;Westerterp et al, 1992), and the Baecke obtained very good results at 5 months and good results at 11 months retest (Pols et al, 1996;Voorrips et al). The reproducibility of the PAQE was found to be very good (Voorrips et al), and the PAQ produced good results (Cauley et al, 1987).…”
Section: Measurement Propertiesmentioning
confidence: 97%
“…The rightmost columns of Table 1 detail the acceptability, practicality, and feasibility of the measures. In terms of Bonnefoy et al, 1996; k Pols et al, 1996. acceptability and practicality, the PASE and the YPAS were the best contenders, and the PAQ, PASE, and LHFQ had the best feasibility because of their versatile administration modes. Table 4 illustrates the advantages and disadvantages of each measure in relation to practical applications.…”
Section: Direct Validitymentioning
confidence: 99%
“…Eleven studies were conducted in a mixed-gender sample (20,25,26,30,32,33,43,44,(46)(47)(48), four among a male sample (34,36,40,41) and three studied females only (21,22,50). The average age of the study populations ranged from ~16-71 years, samples sizes varied from 19-2240.…”
Section: Construct Validitymentioning
confidence: 99%